Impact of Forest Dieback on Hydrology and Nitrogen Export Using a New Dynamic Water Quality Model - Mufeng Chen; Seifeddine Jomaa; Angela Lausch; Burkhard Beudert; Salman Ghaffar; Wenhao Jia; Michael Rode (Water Resources Research)
Abstract Forest status is crucial for catchment hydrology and water quality but is increasingly disturbed by human activities and climatic factors. Therefore, it is urgently necessary to develop water quality models that can adapt to these changes. This study used a new dynamic Hydrological Predictions for the Environment (HYPE) model to assess the effect of rapid and continuous forest changes on catchment hydrology and nitrogen export. The modified HYPE model was implemented for the 25 years period in the Große Ohe catchment in Germany, which has experienced severe forest dieback and recovery. Due to the stochastic nature of infestation events, data covering the entire process of forest change are rare. The modified HYPE model performed well at different scales for discharge and dissolved inorganic nitrogen (DIN) export. It was able to (a) capture the timing of peak flows and the seasonal DIN concentration dynamics and (b) reflect the initial increase and subsequent decrease trend in discharge and DIN export in accordance with forest dieback and regeneration. The increase in nitrogen export after forest dieback primarily resulted from reduced forest uptake and increased soil nitrogen availability from tree residues. The difference in runoff and nitrogen export increment with or without regeneration highlights the importance of forest regeneration in restoring catchment hydrology and water quality. Additionally, a decrease in DIN export after residue removal implies the impact of sound post‐disturbance management strategies. The dynamic modeling under changing catchment forests can enhance the analysis of catchment water quality and effectively support forest management.